Encouraging Faculty Adoption of Virtual Reality Tools in Engineering Education - Sarah El-Mallah; Tonia Dousay (Issues and Trends in Educational Technology, 2019)
Virtual reality is one of the widely emerging technologies and is anticipated to play a substantial role in the future of education. Though many research studies have been conducted on its application in various disciplines, less investigations focused on its integration in engineering higher education. This work, thus, aims to identify the major opportunities and challenges of virtual reality adoption in various areas of engineering. To do so, solicited engineering faculty participants from four different departments at the University of Idaho attended demos to examine a virtual reality technology – namely Leap Motion desktop controller. They were then asked to respond to a survey that collected their feedback on virtual reality possible applications, educational uses, and challenges in their respective disciplines. The survey also collected responses related to their perception, acceptance, and recommendations on ways to encourage virtual reality implementation. Results show a majority of participants being in favor of adopting virtual reality, suggesting areas and classes/labs that would best benefit from such technology. This paper also proposes professional development activities and suggestions for virtual reality applications’ developers.